Un militar realista en la independencia de México Diario personal del oficial de infantería Modesto de la Torre (29 de mayo 1821 - 4 de junio 1822) - Guarisco, Claudia (Sources de la Casa de Velázquez, 2021)
The personal diary that Modesto de la Torre wrote between 1821 and 1822 reflects the perceptions of a young royalist military man about a New Spain that was gaining independence from the Peninsula to become a Mexican Empire. The author traveled from Cadiz to Mexico City with the retinue that accompanied the last viceroy, Juan O'Donojú, and in his pages he describes the nature, towns and cities he passed through, as well as the political and military events that took place during those years. Anecdotes, both major and minor, are found in these brief chronicles. In addition, the dialogue with himself, through writing, is a means to exorcise the crisis of the culture of masculinity that was part of his imaginary. This crisis was largely caused by the nationalist discourse of the Mexicans and their military victories, which became the central theme of his reflections and is extensively analyzed in the study that precedes the transcription of the diary. The spontaneous and secret character of the Apuntaciones makes them a singular source for historians of the early 19th century, of nationalism, and of the little-known first-person writings in the Latin American world of the time.